Analisis SWOT Universitas Melaka sebagai Strategi Pengembangan Universitas Nahdlatul Ulama Surakarta - Muslihudin Bani Muhtarom; Faizul Muna; Siti Jaroyatun Nikmah; Khoirul Anwar (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to analyze the SWOT of the University of Melaka Malaysia to formulate a development strategy for the University of Nahdlatul Ulama Surakarta. Research Methodology: This type of research includes qualitative field research and uses SWOT analysis as an analytical knife. Data collection techniques included interviews, documentaries,, and observation methods from February 12 to 15, 2023 at the University of Melaka Malaysia. Results: The findings of this study indicate that four alternatives can be developed for Universitas Nahdlatul Ulama Surakarta: SO, WO, ST, and WT strategies. The SO strategy includes institutions, curricula, and student development. The two WO strategies covered employment, infrastructure, and student affairs. The three ST strategies are curriculum, institutions, management, and infrastructure. The four WT strategies covered infrastructure, foreign relations, employment, and student affairs. Limitation: This study focuses on two tertiary institutions, namely the University of Melaka and the University of Nahdlatul Ulama Surakarta. Contribution: First, it can be used as evaluation material for the University of Melaka. Second, it can be an opportunity for Nahdlatul Ulama University to collaborate with the University of Melaka as a higher education development strategy. Novelty: Based on the literature review that the authors explain in this article, it shows that the renewal of this research is to use the results of the SWOT analysis at Melaka University to formulate a development strategy for Nahdlatul Ulama University, Surakarta.